Corrosion behavior of Cr-bearing steels in CO2-O2-H2O multi-thermal-fluid environment. (21st October 2020) - Yuan, Juntao; Zhu, Kaifeng; Jiang, Jingjing; Zhang, Huihui; Fu, Anqing; Li, Wensheng; Yin, Chengxian; Li, Fagen
Abstract: Multi-thermal fluid is used to enhance heavy oil recovery, but it also causes severe corrosion failure of metallic tubing and its mechanism is still open to debate. In the present work, the c orrosion behavior of commercial steels with different Cr content (3 wt%, 9 wt%, and 25 wt%) in simulated CO2 -O2 -H2 O multi-thermal fluid environments were studied by immersion corrosion test and microstructural characterization. The results exhibit that the Cr content of steel determines the type of corrosion products. The less protective corrosion scale is mainly composed of FeCO3, (Fe, Cr)3 O4, and Fe2 O3, which is formed on the surface of 3Cr and 9Cr steels. The protective corrosion scale is mainly Cr2 O3, which is formed on the surface of 25Cr steel. Only when the Cr content in steel is sufficient (i.e. 25 wt%) to repair the serious depletion of Cr in the metal near the scale/metal interface in time, can protection of the corrosion scale be sustained, to improve its ability to resist the corrosion of multi-thermal fluids.